PHILIP C. BANTIN, ed., Building Trustworthy Digital Repositories: Theory and Implementation - Otte, Maxwell (Archivaria, 2018)
Building Trustworthy Digital Repositories: Theory and Implementation. Philip C. Bantin, ed. Lanham, MD: Rowman & Littlefield, 2016. xv, 371 pp. ISBN 978-1-4422-6378-9